KAJIAN PENGEMBANGAN KAWASAN KONSERVASI PENYU SEBAGAI KAWASAN EKOWISATA DI DUSUN TULANG DESA BARUGAIYA KABUPATEN KEPULAUAN SELAYAR - Rismang, Rismang; Rauf, Abdul; Rustam, Rustam (Universitas Negeri Makassar, 2018)
This study aims to determine what actually as an eco area as a center of ecotourism and turtle area development strategy as an ecotourism area in Tulang village Barugaiya Village Selayar Islands District. Studies show that these results show the uniformity of ecotourism land in the Coastal Area of Tulang is a location with the suitability of the turtle ecotourism location of 1.92 Ha located on station 1 and 3rd station and not 1.52 Ha in station 2. Strategy Development of turtle ecotourism with the results, determined by 10 strategies The best development of turtle ecotourism in Tulang Village Barugaiya Village Selayar Islands District, among others (1) encourage the government in terms of determining the turtle conservation area, (2) the need for more activities to provide facilities (3) socializing stakeholder spatial legislation to avoid conflict and increase community participation, (4) more importance from stakeholders for increased potential of the region, (5) training on human resources related to human resources , (6) application of understanding related to ecosystem destruction turtle nesting areas as well as law enforcement from the government, (7) spatial planning of tourist sites (8) public education about the importance of turtles, (9) planting of mangrove species and coastal vegetation (10) applying fair system in management policy